MHC-I alleles mediate clearance and antibody response to the zoonotic Lassa virus in Mastomys rodent reservoirs. - Ayodeji Olayemi; Dominik Werner Schmid; Ramona Fleischer; Kerstin Wilhelm; Alexander Christoph Heni; Nadine Mueller-Klein; Lavinia Haikukutu; Elisabeth Fichet-Calvet; Stephan Günther; Simone Sommer (Public Library of Science (PLoS), 2024)
West African Mastomys rodents are the primary reservoir of the zoonotic Lassa virus (LASV). The virus causes haemorrhagic Lassa fever and considerable mortality in humans. To date, the role of Mastomys immunogenetics in resistance to, and persistence of, LASV infections is largely unknown. Here, we investigated the role of Major Histocompatibility Complex class I (MHC-I) on LASV infection status (i.e., active vs. cleared infection, determined via PCR and an immunofluorescence assay on IgG antibodies, respectively) in Mastomys natalensis and M. erythroleucus sampled within southwestern Nigeria. We identified more than 190 and 90 MHC-I alleles by Illumina high throughput-sequencing in M. natalensis and M. erythroleucus, respectively, with different MHC allele compositions and frequencies between LASV endemic and non-endemic sites. In M. natalensis, the MHC allele ManaMHC-I*006 was negatively associated with active infections (PCR-positive) and positively associated with cleared infections (IgG-positive) simultaneously, suggesting efficient immune responses that facilitate LASV clearance in animals carrying this allele. Contrarily, alleles ManaMHC-I*008 and ManaMHC-I*021 in M. natalensis, and MaerMHC-I*008 in M. erythroleucus, were positively associated with active infection, implying susceptibility. Alleles associated with susceptibility shared a glutamic acid at the positively selected codon 57, while ManaMHC-I*006 featured an arginine. There was no link between number of MHC alleles per Mastomys individual and LASV prevalence. Thus, specific alleles, but not MHC diversity per se, seem to mediate antibody responses to viremia. We conclude that co-evolution with LASV likely shaped the MHC-I diversity of the main LASV reservoirs in southwestern Nigeria, and that information on reservoir immunogenetics may hold insights into transmission dynamics and zoonotic spillover risks.